Kematian dan Kebangkitan Jurnalisme: - Michael Carlos Kodoati (Lumen Veritatis: Jurnal Filsafat dan Teologi, 2024)
In his critique of the mass media, Habermas maintains that the media is inappropriate for democracy. Because of its proclivity to favor money and political power, Habermas believes that the media can no longer serve as a democratic outlet. Sandra L. Borden showed that the media, whatever it is, is able to assist democracy. Journalism has a solid heritage as long as it adheres to democratic, citizenship, knowledge, and freedom principles. In that sense, both Habermas and Borden believe journalism to be extinct. The article aims to find a way out of Habermas and Borden's simultaneous assessment of journalism's end. Today, when untruths may be camouflaged as facts and the people choose social media to determine the truth, the function of journalism expected by Habermas and Borden is truly required. What is democracy if there are no watchdogs? The author is looking to highlight the importance of self-improvement in the press and journalism through the way of analyzing literature sources. Both Habermas and Borden maintain that the press and journalism must follow a democratic path if they are to be independent and not be influenced by money and political power. In accordance to the author, an appropriate channel within a democratic framework is required to ensure that every truth and public opinion eventually contributes to the healthy growth of democracy.